PEMBERIAN LAYANAN BIMBINGAN BELAJAR GUNA MEMBANTU MENGATASI PERMASALAHAN KEKURANGAN TENAGA PENGAJAR DI SDN KLASEMAN - Suryani, Ida Sugeng; Hidayat, Moch Ryan Nur; Alam, Mihbub; Mustafida, Mustafida; Sandi, Eriska Nofia (Abdi Panca Marga, 2023)
One of the services offered to the community of KKN students by Panca Marga University is to increase the interest of students in reading in Klaseman village in Gending District. The aim of this activity is to prepare a competent, broad-minded and book-loving generation. Students' interest in reading is manifested in formal and informal educational settings. In free education, studies are organized for students, while formal studies are organized in preschools, kindergartens and primary schools. Students teach and assist students in acquiring basic reading skills. Students make the classroom atmosphere as lively as possible to attract students' attention so that students can focus on learning. Student observation method used. The book in question is a book adapted to the criteria for early children's books. Early childhood books are usually dominated by attractive images and colors. These images are meant to inspire children's imaginations and teach them to be sensitive and caring about the things they encounter. It is best to get concentration help while reading books. Keywords: Children, Reading, Literacy, Interests.